Slip angle control based DTC of open-end winding induction motor drive using dual randomized decoupled PWM for acoustic noise mitigation in EV application - Challa, Ganesh; Reddy, M. Damodar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Reduced vibration, acoustic noise, and higher DC link utilization are advantageous for industrial drives and/or electric vehicle (EV) drives. Direct torque controlled (DTC) induction motor drives fulfill the stringent demands of the EV and/or industries of the modern era. However, torque and flux ripples occur at steady state conditions, resulting in increased acoustical noise. As a result, EV and/or workplace noise has emerged as a major issue, both in terms of human health and safety. The space vector pulse width modulation (SVPWM) improves DC bus utilization. However, SVPWM is less effective in reducing acoustic noise. Many random PWM (RPWM) approaches, including random zero vector PWM (RZVPWM), random pulse position modulation (RPPM), random carrier frequency modulation (RCFM), and RCFM-RPPM are effective in reducing acoustic noise. However, due to the decreased level of randomization, reducing noise remains problematic. This research proposes a decoupled hybrid dual randomized RPWM (HDRRPWM) schemes for slip angle control based DTC of an open-end winding induction motor drive for acoustic noise mitigation in EV applications. The suggested schemes aim to demonstrate the efficacy of HDRRPWMs in dispersing the acoustic noise spectrum as compared to traditional methods.